Efektivitas pendidikan kesehatan reproduksi berbasis sekolah: A literature review - Nurhayati, Nurhayati; Fatila, Nabila; Utami, Risna; Afnanin, Fabi Ayyi; Ramadhan, Muhammad Rizky (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: School-based reproductive health education is important to improve adolescent knowledge and behavior related to reproductive health. With issues such as teenage pregnancy and sexually transmitted diseases, schools play a vital role in providing accurate information for adolescents to make healthy decisions. Purpose: To analyze the effectiveness of school-based reproductive health education. Method: The qualitative research was based on a literature review by collecting 10 relevant scientific journals from the last 5 years. Data from the journals were analyzed in depth to identify key trends and findings related to the implementation of reproductive health education programs in schools. Results: The results showed that school-based reproductive health education was effective in improving students' understanding of topics such as reproductive organ functions, the risks of risky sexual behavior, and prevention of sexually transmitted diseases. Interactive learning methods, the involvement of trained teachers, and parental and community support were the main factors in the success of this program. In addition, an adaptive approach to local cultural values ​​also supported the acceptance of the program in various regions. Conclusion: School-based reproductive health education contributes significantly to building healthy reproductive knowledge and behaviors in students. However, the sustainability of the program requires systematic monitoring and evaluation to ensure its long-term effectiveness. Keywords: Education; Reproductive Health; School Based. Pendahuluan: Pendidikan kesehatan reproduksi berbasis sekolah penting untuk meningkatkan pengetahuan dan perilaku remaja terkait kesehatan reproduksi. Dengan masalah seperti kehamilan remaja dan penyakit menular seksual, sekolah berperan vital dalam memberikan informasi yang tepat bagi remaja agar dapat membuat keputusan sehat. Tujuan: Untuk menganalisis efektivitas efektivitas pendidikan kesehatan reproduksi berbasis sekolah. Metode: Penelitian kualitatif berbasis tinjauan literatur dengan mengumpulkan 10 jurnal ilmiah yang relevan dari 5 tahun terakhir. Data dari jurnal dianalisis secara mendalam untuk mengidentifikasi tren dan temuan utama terkait implementasi program pendidikan kesehatan reproduksi di sekolah. Hasil: Pendidikan kesehatan reproduksi berbasis sekolah efektif dalam meningkatkan pemahaman siswa tentang topik seperti fungsi organ reproduksi, risiko perilaku seksual berisiko, dan pencegahan penyakit menular seksual. Metode pembelajaran interaktif, keterlibatan guru yang terlatih, serta dukungan orang tua dan komunitas menjadi faktor utama keberhasilan program ini. Selain itu, pendekatan yang adaptif terhadap nilai-nilai budaya lokal turut mendukung penerimaan program di berbagai wilayah. Simpulan: Pendidikan kesehatan reproduksi berbasis sekolah berkontribusi signifikan dalam membangun pengetahuan dan perilaku reproduksi yang sehat pada siswa. Namun, keberlanjutan program membutuhkan monitoring dan evaluasi yang sistematis untuk memastikan efektivitas jangka panjangnya. Kata Kunci: Berbasis Sekolah; Kesehatan Reproduksi; Pendidikan.